2022
DOI: 10.1186/s12887-022-03726-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infections in X-linked hyper-IgM syndrome with CD40LG mutation: a case series of seven children in China

Abstract: Background X-linked hyper-immunoglobulin M (XHIGM), a primary immunodeficiency syndrome caused by mutations in the CD40 ligand gene(CD40LG), presents with recurrent respiratory infections in pediatric patients. We aimed to evaluate the spectrum of clinical features and respiratory pathogens in pediatric patients with XHIGM in China. Methods We retrospectively reviewed seven pediatric patients who were diagnosed with XHIGM and received follow-up tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While MSMDs were initially recognized for their distinct susceptibility to mycobacteria (particularly non-tuberculous (NTM) and occasionally M. tuberculosis ) and Salmonella (predisposing victims to extra-intestinal salmonellosis) [ 38 , 39 , 150 , 151 , 152 , 153 , 154 ], they were also subsequently found in patients with otherwise unexplained disseminated TDEF infection, including histoplasmosis (IL12RB1 [ 153 , 155 , 156 , 157 ]; IFNGR1 [ 158 ]), coccidioidomycosis (IFNGR1 [ 159 ] and IL12RB1 [ 160 ]), and paracoccidioidomycosis (IL12RB1 [ 161 ]). These findings provided the framework of human immunity to TDEF, which was followed by the identification of other IEI congruent with defective IFN-γ-mediated immunity, including CD40L deficiency [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ] (discussed further in the section on “Pneumocystis”), GATA2 deficiency [ 171 ], and STAT1 GOF [ 168 , 169 , 172 , 173 ].…”
Section: Thermally Dimorphic Endemic Mycosesmentioning
confidence: 99%
“…While MSMDs were initially recognized for their distinct susceptibility to mycobacteria (particularly non-tuberculous (NTM) and occasionally M. tuberculosis ) and Salmonella (predisposing victims to extra-intestinal salmonellosis) [ 38 , 39 , 150 , 151 , 152 , 153 , 154 ], they were also subsequently found in patients with otherwise unexplained disseminated TDEF infection, including histoplasmosis (IL12RB1 [ 153 , 155 , 156 , 157 ]; IFNGR1 [ 158 ]), coccidioidomycosis (IFNGR1 [ 159 ] and IL12RB1 [ 160 ]), and paracoccidioidomycosis (IL12RB1 [ 161 ]). These findings provided the framework of human immunity to TDEF, which was followed by the identification of other IEI congruent with defective IFN-γ-mediated immunity, including CD40L deficiency [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ] (discussed further in the section on “Pneumocystis”), GATA2 deficiency [ 171 ], and STAT1 GOF [ 168 , 169 , 172 , 173 ].…”
Section: Thermally Dimorphic Endemic Mycosesmentioning
confidence: 99%
“…The decreased Th17 differentiation impairs IL-17 function in the defense against extracellular pathogens like fungi, which might explain the patient’s susceptibility to T.marneffei [ 32 , 33 ]. CD40LG mutation can cause X-linked hyper-immunoglobulin M (XHIGM), which has been classified as combined T and B immunodeficiency [ 34 ]. A hemizygous mutation of IL2RG was identified in one patient diagnosed with SCID [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…After receiving anti-fungal treatment and IVIg replacement, the patient underwent allogeneic stem cell transplantation, eventually being discharged in good condition [ 28 ]. Another study by Fan et al showed that children with XHIGM were more vulnerable to respiratory infections, including T. marneffei , which in turn would help pediatricians to identify XHIGM [ 29 ]. Hence, in order to avoid life-threatening infection, allogeneic stem cell transplantation should be carried out once the patient is diagnosed with XHIGM.…”
Section: Discussionmentioning
confidence: 99%